Ritual Plants of Maharashtra: Documentation, Analysis, and Cultural Significance - Karle B.A; Kulkarni A.A; Deshmukh S.R; Pansare P.A.; Lamrood P.Y (The Bioscan, 2025)
Festivals are integral to human culture, celebrating significant life events and spiritual occasions. Traditional festivals reflect cultural identity, fostering community and spirituality. Plants play a crucial role in these celebrations worldwide, symbolizing cultural heritage and the human-nature relationship. In India, their significance extends beyond practical use, yet research on their cultural importance remains limited.This study documents and statistically analyzes plant usage in 19 Indian festivals across different seasons. Food-related plants are central to many celebrations, with Haritalika showing the highest plant usage. Arecaceae and Poaceae are the most commonly used families, with key plants including nagli, coconut, mangoes, and nuts. Word cloud analysis highlights prominent plant-related festivals such as Gopalkala, Pola, Mangalagaur, and Diwali.A Chi-square test revealed a highly significant association between festivals and seasons (X² = 820, df = 72, p < 2.2e-16), confirmed by Cramér’s V (1) and the contingency coefficient (0.894). Flower and tree usage showed strong associations with Marathi and English months (Φ = 0.512 and Φ = 0.410, respectively). Flower (Φ = 0.412) and powder (Φ = 0.417) usage were significantly linked to festivals, highlighting their importance in religious and celebratory practices. Sentiment analysis assigned scores to plant-related phrases, indicating mild positivity for "food, worshipping" (0.4596) and neutrality for "prasad" and "decoration" (0.0000). Network analysis revealed distinct clusters of festivals and seasons, emphasizing shared cultural and temporal connections. Correspondence analysis biplots showed strong seasonal associations, with Gregorian calendar months exhibiting clearer temporal fixation than the Hindu lunar calendar.This study enhances understanding of the cultural significance of plants in festivals, reinforcing their role in biodiversity conservation and cultural heritage preservation.